Hydrolytic transformation mechanism of tetracycline antibiotics: Reaction kinetics, products identification and determination in WWTPs - Zhong, Shao-Fen; Yang, Bin; Xiong, Qian; Cai, Wen-Wen; Lan, Zheng-Gang; Ying, Guang-Guo (Ecotoxicology and environmental safety, 2022)
Antibiotic residues and antibiotic resistance have been widely reported in aquatic environments. Hydrolysis of antibiotics is one of the important environmental processes. Here we investigated the hydrolytic transformation of four tetracycline antibiotics i.e. tetracycline (TC), chlortetracycline (CTC), oxytetracycline (OTC) and doxycycline (DC) under different environmental conditions, and determined their parents and transformation products in the wastewater treatment plants (WWTPs). The results showed that the hydrolysis of the four tetracyclines followed first-order reaction kinetics, and the acid-catalyzed hydrolysis rates were significantly lower than the base-catalyzed and neutral pH hydrolysis rates. The effect of temperature on tetracycline hydrolysis was quantified by Arrhenius equation, with Ea values ranged from 42.0 kJ mol−1 to 77.0 kJ mol−1 at pH 7.0. In total, nine, six, eight and nine transformation products at three different pH conditions were identified for TC, CTC, OTC and DC, respectively. The main hydrolysis pathways involved the epimerization/isomerization, and dehydration. According to the mass balance analysis, 4-epi-tetracycline and iso-chlortetracycline were the main hydrolytic products for TC and CTC, respectively. The 2 tetracyclines and 4 hydrolysis products were found in the sludge samples in two WWTPs, with concentrations from 15.8 ng/g to 1418 ng/g. Preliminary toxicity evaluation for the tetracyclines and their hydrolysis products showed that some hydrolysis products had higher predicted toxicity than their parent compounds. These results suggest that the hydrolysis products of tetracycline antibiotics should also be included in environmental monitoring and risk assessment. [Display omitted] •Hydrolysis of 4 typical tetracyclines was investigated according to OECD Guideline.•The half-lives of tetracycline hydrolysis were in the range of 20.6–106.6 days.•The 32 hydrolysis products were detected and 5 reaction pathways were proposed.•Some hydrolysis products had higher toxicity than their parent compounds.•Six target substances were identified in two WWTPs by suspect screening.